Molecular structure and biological activities of 4-thiazolidinone derivatives: a combined theoretical and experimental study. (1st February 2023) - Mushtaque, Md.; Avecilla, Fernando; Alsukaibi, Abdulmohsen Khalaf Dhahi; Pingale, Subash S.; Kamble, Kirtee M.; Rizvi, M. Moshahid A.
Abstract: In this study, we report the structural and biological characterization of (2 Z, 5Z)-5-(4-methyl benzylidene)-3-(2-methylpropyl)-2-(phenylimino)-1, 3-thiazolin-4-one (6a ) and (2 Z, 5 Z )-5-(3-chlorobenzylidene)-3-(2-methylpropyl)-2-(phenylimino)-1, 3-thiazolin-4-one (6b ). These compounds were synthesized following the reported method and the molecular structures were confirmed by single-crystal X-ray diffraction studies. Density functional theory (DFT) calculation was carried out to complement the structural and spectral features. In vitro cytotoxicity of the compounds was tested against both the cancerous (SW-480 & MCF-7) and normal (HEK-293) cell lines using the MTT assay. The results indicated that compounds adopted (Z, Z)–configuration with respect to the exocyclic methylene proton and the exocyclic nitrogen. It was observed that compound 6a (IC50 = 190 ± 0.23 μg/mL on SW-480 & IC50 = 330 ± 0.27 μg/mL on MCF-7) showed a weaker anti-proliferative effect than 6b (IC50 = 119.87 ± 0.24 μg/mL on SW-480 & IC50 = 140.39 ± 0.28 μg/mL on MCF-7). These compounds showed acceptable toxicity on normal cell line. GRAPHICAL ABSTRACT: UF0001